Elevated depressive symptoms among newer and younger healthcare workers in Japan during the COVID‐19 pandemic. Issue 4 (3rd November 2021) - Katsuta, Narimasa; Ito, Kanami; Fukuda, Hiroshi; Seyama, Kuniaki; Hori, Satoshi; Shida, Yuka; Nagura, Rie; Nojiri, Shuko; Sato, Hiroyuki
Abstract: Aim: Depression is a frequent outcome of long‐term stress, but no studies have examined depression rates among Japanese healthcare workers fighting the COVID‐19 pandemic. Therefore, we conducted a web‐based interview of hospital employees to assess depression prevalence and factors. Methods: This observational cohort study was conducted from July to August, 2020, as part of a mandatory health checkup of Juntendo University Hospital employees (Tokyo, Japan). A total of 4239 participants completed a web‐based questionnaire on medical history and current health status. The Center for Epidemiologic Studies Depression Scale (CES‐D) was used for self‐assessment, with a score of ≥16 considered to indicate depression. Results: Among all employees, the proportion of depression was 31.3% in 2020, the highest measured in the last 10 years and substantially greater than the pre‐pandemic value in 2019 (27.5%). The proportion of depression for 2020 was significantly higher in new recruits than in employees with more than 2 years of experience (47.0% vs 29.9%, respectively, P < .0001) and in new recruits in 2019 (26.4%, P < .0001). When subdivided by occupation, nurses demonstrated the highest depression rate (43.2%), followed by paramedics (35.1%) and clerks (31.6%), whereas residents (22.9%), doctors (20.4%), teaching staff (18.0%), and part‐time staff (15.3%) reported lower depression rates. The positive CES‐D score significantly correlated with age ( P < .0001). Conclusions: Younger and newer employees demonstrated the highest rates of depression independent of occupation. Therefore, mental healthcare programs focusing on these vulnerable groups need to be established. Abstract : Younger and newer employees demonstrated the greatest rates of depression independent of occupation. Mental healthcare programs focusing on these vulnerable groups are required.